Facile ultrasonication approach for the efficient synthesis of ethylene glycol-based thermoresponsive nanogels - Biglione, Catalina (2015)
The employment of nanogels (NGs) for drug delivery purposes has experienced a huge increase during thelast decades. Among the different NGs, those displaying stimuli-responsive properties are of special interest.In particular, NGs that are able to swell or shrink by the action of temperature are very promising materialsfor applications in the biomedical and biological fields. In this work we present the preparation ofthermoresponsive ethylene glycol-based NGs employing a simple and reliable ultrasonication approach.By this means, the reaction times could be shortened and the NGs formation could be performed evenat room temperature and in the presence of oxygen. The NGs have been characterized by differenttechniques and their cloud point could be tuned by changing the molar ratio between the monomers.Finally, the NGs were labelled with Rhodamine B and their cellular uptake and cytotoxicity have beenanalysed.